Enzymatic esterification of dihydrocaffeic acid and evaluation of antioxidant activities of the synthesized alkyl-esters - Gholivand, Somayeh (2016)
Solubility limitations of phenolic acids in many lipidic environments restrict their application as effective antioxidants. Enzymatic esterification of phenolic acids in a green media such as ionic liquid improves the lipophilicity of the resultant compounds. Herein, the investigation of a biocatalysts process for the esterification of dihydrocaffeic acid with different ionic liquids in order to improve the conversion of the phenolic acid in a shorter time and increase productivity of target product was carried out. To achieve the maximum conversion yield, the lipophilization of dihydrocaffeic acid (DHCA) by its enzymatic esterification with hexanol in the selected ionic liquid (as a model) was optimized by response surface methodology (RSM) using a five-level and four independent variables including: dosage of the enzyme (in relation to the total weight of substrates), hexanol/dihydrocaffeic acid mole ratio, reaction temperature and reaction time. The obtained optimal conditions were applied for the synthesis of the other n-alkyl esters with different chain lengths. Subsequently, the synthesized esters were separated from unreacted compounds and purified via a silica gel column. The purified alkyl-esters were identified by Fourier transform infrared (FTIR) and Nuclear magnetic resonance (NMR) analysis. Finally, the effects of alkyl chain length and concentration on the anti-oxidative properties of the resultant purified esters was investigated using β-carotene bleaching (BCB) and free radical scavenging method DPPH and also compared with butylated hydroxytoluene (BHT) as reference compound. According to the attained results, among ionic liquids tested, 1-butyl-3-methylimidazolium bis (trifluoromethylsulfonyl) imide was the best solvent with the highest bioconversion. Furthermore, results of the optimization showed that hexyl dihydrocaffeate (HDHCA) conversion yield was significantly (p<0.05) affected by the linear, quadratic and the interaction effects of all the variables examined. Thus, an empirical equation was developed to describe and predict the variation of the response variable. The optimization procedure showed that the optimum molar conversion yield for hexyl dihydrocaffeate (HDHCA) (Y1 = 84.41%) was obtained using 41.6% enzyme load at 39.4oC for 77.5 h and 9.3 × 10-4 mM hexanol to DHCA ratio. According to the obtained results from synthesized alkyl esters, both esters’ concentration and their chain-length had significant (p<0.05) effects on their antioxidant assays. Moreover, the scavenging activity of the tested compounds was methyl ester > hexyl ester > dodecyl ester > octadecyl ester > BHT while the order of BCB anti-oxidative activity was BHT > octadecyl ester > dodecyl ester > hexyl ester > methyl ester. Therefore, in the emulsion system, the hydrophobicity and solubility of the tested esters affected the antioxidant activity of esters which revealed that the antioxidant with hydrophobic character had better anti-oxidative activity in an emulsion system.